METODE ALGORITMA PENENTUAN KEPUTUSAN TERKAIT PEMBELIAN OBAT - Tangkas, Hansel Hens; Yuwindry, Iwan; Abdi, Muhammad Mahendra; Melviani, Melviani; Gumarus, Ellora Griselda; Syahran, Dayna Maharani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Medication is one of the important or primary needs in health services used by the community. Cases of acute renal failure totaled 326 cases with 204 children dying as of July 19, 2023. A study explains that the safety of a product is significantly related to purchasing decisions. Decision methods related to drug purchases have never been found until now. Feelings of indecision or anxiety due to the rampant cases of acute renal failure can be eliminated by the existence of a method or fixed scale. This study generally aims to help the community in determining drug purchase decisions through a method. The design in this study is to use a descriptive observational design with a survey research design. Data were obtained by interview and analyzed by making verbatim tables. Then, the algorithm was tested for validity and reliability on 30 samples. The results explained that the interviewees prioritized quality, price, and opinions from others in deciding to buy drugs. Researchers created an algorithm based on indicators of drug purchase decisions, including drug needs, drug usage history, drug information, and drug needs. The algorithm has been said to be valid as evidenced by the value of r count> r table and reliable as an instrument that helps people determine as evidenced by the value of Cronbach's Alpha> 0.6. Indicators of drug purchase decisions are influenced by drug usage history, drug needs, drug information, and drug needs. The algorithm created has been tested valid and reliable.